2015
DOI: 10.1016/j.ces.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate growth at the interface between water and pure or mixed CO2/CH4 gases: Influence of pressure, temperature, gas composition and water-soluble surfactants

Abstract: International audienceThe morphology and growth of gas hydrate at the interface between an aqueous solution and gaseous mixtures of CO2 and CH4 are observed by means of a simple experimental procedure, in which hydrate formation is triggered at the top of a sessile water drop by contact with another piece of gas hydrate and the ensuing hydrate growth is video-monitored. The aqueous solution is either pure water or a solution of a nonionic or anionic surfactant at low concentration (in the 100-1000ppmw range). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 44 publications
4
53
0
Order By: Relevance
“…AOT is considered a double-tailed surfactant, which requires lower dosage compared to SDS for the same decrease in surface tension and activity at the interface between water and hydrate. 41,42 This already indicates that at the same concentration the accelerating effect on the gas hydrate formation should be higher for AOT, as observed.…”
Section: Mechanistic Interpretationsupporting
confidence: 63%
“…AOT is considered a double-tailed surfactant, which requires lower dosage compared to SDS for the same decrease in surface tension and activity at the interface between water and hydrate. 41,42 This already indicates that at the same concentration the accelerating effect on the gas hydrate formation should be higher for AOT, as observed.…”
Section: Mechanistic Interpretationsupporting
confidence: 63%
“…As in the study of Daniel-David et al (2015), we observed two different growth patterns. One for the systems with pure CH 4 and the 25:75 gas mixture, and the other for those with pure CO 2 and the 75:25 gas mixture.…”
Section: Effect Of the Surfactant Carbon-chain Length And Gas-phase Cmentioning
confidence: 70%
“…in a recent article byDaniel-David et al (2015). In our experiments, cell pressure and cell temperature were the same as those reached by the system just before the THF injection in the experiments conducted in the reactor cell, namely P = 2.8 MPa, 3.4 MPa, 4.3 MPa and 5.1 MPa for the CO 2 , the 75:25 and 25:75 gas mixtures, and the CH 4 respectively, and T = T targ (= 275 K).…”
mentioning
confidence: 96%
“…In the aspect of fundamentals, the aforementioned context reflects a lack of a universal understanding of the microscopic pathway of surfactant effects, especially in low concentration regime. Indeed, the fact that current literature neglects the importance of interfacial water when discussing the influence of surfactants (on gas hydrate formation) is of major shortcoming because the interface between gas and water has been observed to be the starting points of gas hydrate nucleation [39][40][41] . In other words, local water molecules at gas-water interface involve directly in the nucleation of gas hydrate whereby they undergo structural rearrangement and transformation.…”
mentioning
confidence: 99%